2016
DOI: 10.1007/s00213-016-4219-8
|View full text |Cite
|
Sign up to set email alerts
|

The effects anandamide signaling in the prelimbic cortex and basolateral amygdala on coping with environmental stimuli in rats

Abstract: RATIONALE: Several lines of recent evidence suggest that endocannabinoids affect behavior by influencing the general patterns of challenge responding. OBJECTIVES: Here we investigated the brain mechanisms underlying this phenomenon in rats. METHODS: The anandamide hydrolysis inhibitor URB597 was condensed into the tip of stainless steel cannulae, which were chronically implanted slightly above the prelimbic cortex (PRL) or the basolateral amygdala (BLA), two important regions of coping and endocannabinoid acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…However, the anxiolytic effects of decreased FAAH activity are notably more prominent under conditions of high environmental aversiveness (Patel et al, 2017) and FAAH inhibition has also been shown to attenuate stress‐induced reductions in salience and reward‐seeking behavior (Rademacher et al, 2008). Further, FAAH and endocannabinoid tone may influence coping behavior such that FAAH inhibition and increased anandamide promote more focused problem solving in light of anxiety‐inducing environmental stimuli (Aliczki et al, 2016). Finally, alcohol‐related stress response has been shown to be context‐dependent, whereby acute alcohol intoxication dampens aversive stress reactivity to uncertain or variable threat (Bradford et al, 2013; Gorka et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the anxiolytic effects of decreased FAAH activity are notably more prominent under conditions of high environmental aversiveness (Patel et al, 2017) and FAAH inhibition has also been shown to attenuate stress‐induced reductions in salience and reward‐seeking behavior (Rademacher et al, 2008). Further, FAAH and endocannabinoid tone may influence coping behavior such that FAAH inhibition and increased anandamide promote more focused problem solving in light of anxiety‐inducing environmental stimuli (Aliczki et al, 2016). Finally, alcohol‐related stress response has been shown to be context‐dependent, whereby acute alcohol intoxication dampens aversive stress reactivity to uncertain or variable threat (Bradford et al, 2013; Gorka et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to being directly involved in modulating the neuroendocrine stress response, prefrontocortical eCB signaling has been highly implicated in regulating the emotional and behavioral responses to stress exposure. For example, inhibiting AEA hydrolysis in the PL (thereby boosting levels) is able to significantly reduce stress-induced corticosterone release (McLaughlin et al, 2014), attenuate behavioral responses to environmental threat (Aliczki et al, 2016), and reduce anxiety-like behaviors (Rubino et al, 2008b). Conversely, diminishing AEA signaling by overexpressing FAAH in the mPFC elicits a robust anxiogenic phenotype.…”
Section: Prefrontocortical Endocannabinoids As a Stress-buffering Systemmentioning
confidence: 99%
“…However, some determinants, such as intractable somatic pain or psychological distress are essentially unavoidable. Long-term experiences of unavoidable, persistent distress would alter the prefrontal circuits that assess the internal state to decide coping strategies ( Roy et al, 2014 ; Shrestha et al, 2015 ; Aliczki et al, 2016 ; Zhang et al, 2017 ). It is well established that chronic pain, as well as depression, leads to hypodopaminergic tone in the brain ( Niikura et al, 2010 ; Belujon and Grace, 2017 ; Ong et al, 2018 ).…”
Section: Biological Processes Underlying Mpfc-mglur5 Upregulation: Pomentioning
confidence: 99%